Infection and Immunity. (Washington, DC: American society for microbiology, 1984)
Infection and immunity is devoted to the advancement and dissemination of fundamental knowledge concerning infections caused by pathogenic bacteria, fungai and unicellular paracites, the ecology and epidemology of pathogenic microbes, virulence factors such as toxines and microbio surface stractures, nonspecific factors in host resistance unsusceptibility to infection and immunolgy of microbio infections.
Keywords: Infection; Immunity